Human impacts on the world’s raptors - O’Bryan, Christopher J.; Allan, James R.; Suarez-Castro, Andres Felipe; Delsen, Dobrochna M.; Buij, Ralph; McClure, Christopher J. W.; Rehbein, Jose A.; Virani, Munir Z.; McCabe, Jennifer D.; Tyrrell, Peter; Negret, Pablo J.; Greig, Chris; et al. (Frontiers in Ecology and Evolution, 2022)
Raptors are emblematic of the global biodiversity crisis because one out of five species are threatened with extinction and over half have declining populations due to human threats. Yet our understanding of where these ‘threats’ impact raptor species is limited across terrestrial Earth. This is concerning because raptors, as apex predators, are critically positioned in ecological food webs and their declining populations can undermine important ecosystem services ranging from pest control to disease regulation. Here, we map the distribution of 15 threats within the known ranges of 172 threatened and near threatened raptor species globally as declared by the International Union for the Conservation of Nature. We analyse the proportion of each raptor range that is exposed to threats, identify global hotspots of impacted raptor richness, and investigate how human impacts on raptors vary based on several intrinsic (species traits) and extrinsic factors. We find that raptors have 66% of their range potentially impacted by threats on average (range 2.7-100%.) Alarmingly, critically endangered species have 90% of their range impacted by threats on average. We also highlight 57 species (33%) of particular concern that have >90% of their ranges potentially impacted. Without immediate conservation intervention, these 57 species, including the most heavily impacted Forest Owlet (Athene blewitti), the Madagascar Serpent-eagle (Eutriorchis astur), and the Rufous Fishing-owl (Scotopelia ussheri), will likely face extinction in the near future. Global ‘hotspots’ of impacted raptor richness are ubiquitous, with core areas of threat in parts of the Sahel and East Africa where 92% of the assessed raptors are potentially impacted per grid cell (10 species on average), and in Northern India where nearly 100% of raptors are potentially (11 species). Additionally, ‘coolspots’ of unimpacted richness that represent refuges from threats occur in Greenland and Canada where 98% and 58% of raptors are potentially unimpacted per grid cell, respectively (nearly one species on average), Saharan Africa where 21% are potentially unimpacted per grid cell (one species on average), and parts of the Amazon with 12% (0.6 species on average). The results provide essential information to guide conservation planning and action of the world’s imperilled raptors.